2005
DOI: 10.1002/pssa.200521104
|View full text |Cite
|
Sign up to set email alerts
|

From electronic grade to solar grade silicon: chances and challenges in photovoltaics

Abstract: Dedicated to Professor Horst P. Strunk on the occasion of his 65th birthday 71.55.Cn, 72.20.Jv, 72.40.+w, 72.80.Cw, 84.60.Jt Photovoltaics is a promising but challenging opportunity for the environmentally clean production of electric energy, as the cost of the produced energy is still too high to compete with conventional thermal and nuclear sources, in spite of the scientific and technological progress occurred in this field after the first oil crisis of 1973. Among the problems which should be solved to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 48 publications
2
22
0
1
Order By: Relevance
“…The purification of Si and the existence of macrosegregation were shown by Khattak et al [33] in ingots grown by the heat exchanger method (HEM), but the concentration profiles of impurities were not given. Yuge et al [34] and Pizzini et al [35] obtained Si ingots grown by an unspecified directional solidification process and showed concentration profiles of several impurities along the Si ingot, revealing macrosegregation. *From Tang et al [8] For these elements, the solvus line was not available; therefore, the reported solubility in this table is that at the solidus line, at its lowest temperature, where the solvus line should begin.…”
Section: B Macrosegregation In Silicon Ingotsmentioning
confidence: 98%
“…The purification of Si and the existence of macrosegregation were shown by Khattak et al [33] in ingots grown by the heat exchanger method (HEM), but the concentration profiles of impurities were not given. Yuge et al [34] and Pizzini et al [35] obtained Si ingots grown by an unspecified directional solidification process and showed concentration profiles of several impurities along the Si ingot, revealing macrosegregation. *From Tang et al [8] For these elements, the solvus line was not available; therefore, the reported solubility in this table is that at the solidus line, at its lowest temperature, where the solvus line should begin.…”
Section: B Macrosegregation In Silicon Ingotsmentioning
confidence: 98%
“…Its porous structure leads to quantum confinement and an increase in the bandgap, while the increased light absorption results in higher internal quantum efficiency (IQE). The deposition of nanocrystalline Si thin films by low energy plasma enhanced chemical vapour deposition (LEPECVD) reactor is being investigated by the Nanocrystalline Silicon Films for Photovoltaic and Optoelectronic Applications (NANOPHOTO) project [36]. As an alternative to Si photovoltaics, organic solar cells have been developed using TiO 2 nanoparticles coated with an organic dye to convert light into energy by a process analogous to photosynthesis [37,38].…”
Section: Resource Savingmentioning
confidence: 99%
“…This implies to develop low cost production of silicon wafers [2,3], for example ribbon manufacturing processes [4,5] that avoid the loss of silicon when slicing ingots in wafers, or processes using upgraded metallurgical grade (UMG) silicon as a feedstock. Associating ribbon processing with the use of UMG silicon makes it possible to reduce costs twice, because there is no more silicon loss due to slicing, and because one can use less pure silicon feedstock.…”
Section: Introductionmentioning
confidence: 99%